A produção de corporalidades na escola: uma análise do projeto de Educação de Jovens e Adultos em Angra dos Reis. - Galvão, Edna Ferreira Coelho (2004)
To analyze the corporality construction process inside a night school which develops a project designed to adult students who work, requires a history analysis of the body in this Institution, admitting that, at the same time as the school came out, not only productive and unproductive time/space sense began to be built, which maintain itself up to now; but also ruling and disciplinarian body process came about. The bases which instituted the educational system relegated to the body a minor position considering it as a simple host and protector of the mind, which knows and creates everything. In this context, a hierarchical system developed in a way to set the different subjects in specific places and appropriate behavior according to their acquired knowledge power. When a school dares to experiment a different practice, that intends to review space, and mainly, to build more horizontal relationships among the different subjects that make it. It s indispensable to analyze what other senses have been built for the relationships knowledge-power-body in this territory, not to impute a value judgment, but to show a new practice and possibility to perception of new paths. The education of young people and adults is in the context presented as excluding public policies, useful for the control and expansion of a dominant class, and at the same time it is presented as a possibility of equalization of this form of injustice and also as a promoter of good life quality. For this reason, the theses presented resembles the constitution of a city under a dream-migration perspective, desired, and hoped for so many Brazilians who search in the Angra dos Reis lifestyle provenience and emergencies in the educational process and understanding, mainly, the young people and adults educational project for regular municipal night schools. The itinerary for this journey is formed by five stations which correspond to a primary understanding of this research objective and the priorized methodological conceptions; secondly, an overview of the city educational practices and, particularly, that of the Municipal Education Secretary going back to the last three PT (Labor Party) municipal administrations, afterwards, the research tries to understand what is the reserved place for the young and adult student s body within this school/society; for only then to get to know the more universal intentions and implications of the research, and finally visualize, the arriving point with its perceptions concerning area covered and its interferences in my body-experience.